Entrepreneurship and post-pandemic future - Eniola, Anthony Abiodun (Emerald Publishing Limited, 2022)
For many years now, entrepreneurship has been considered one of the most important solutions to the three-pronged challenges - poverty, unemployment, and inequality - of most African countries. COVID-19 has exerted severe damage to economies and businesses globally. For countries in Africa, the implications of COVID-19, on both businesses and individuals, will be enormous as many African societies are rarely equipped to absorb unexpected shocks of this magnitude, as the social and welfare schemes are far below the required levels. Entrepreneurship and Post-Pandemic Future illuminates entrepreneurship in the African setting, focusing on the prospects, challenges as well as the post-pandemic future and captures insights on the impact of COVID-19, the containment strategies that businesses are embracing to cope, and the post-pandemic future. This book will be essential reading to entrepreneurs, governments and government agencies, academics, researchers, and students who are interested in understanding issues relating to entrepreneurship development within the African continent.